2015
DOI: 10.1080/19443994.2013.838519
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of research on microcystins in China and worldwide from 1991 to 2011

Abstract: A B S T R A C TBlue green algae cyanobacterial blooms can produce a family of toxins, microcystins, Microcystis aeruginosa. These proliferate in warm water bodies where nutrients are available, thus drinking water can be contaminated. This study evaluates the scientific output of microcystin research in China relative to that worldwide during 1991-2011 and explores future research directions. Data were retrieved from the online version of Web of Science from 1991 to 2011. Articles referring to microcystins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It is defined as the number of articles with citation numbers higher than or equal to h. In addition, the h-index does not only represent the actual production, but also the apparent influence of a group's or a scholar's published work [18]. Previous research also found that the h-index has a higher predictive potential than the total number of articles published, total number of citations, and average citations per publication [63]. The proceedings tend to have a high h-index.…”
Section: General Characteristics Of Research Publications In Phycobiliproteins Studymentioning
confidence: 99%
“…It is defined as the number of articles with citation numbers higher than or equal to h. In addition, the h-index does not only represent the actual production, but also the apparent influence of a group's or a scholar's published work [18]. Previous research also found that the h-index has a higher predictive potential than the total number of articles published, total number of citations, and average citations per publication [63]. The proceedings tend to have a high h-index.…”
Section: General Characteristics Of Research Publications In Phycobiliproteins Studymentioning
confidence: 99%
“…Bibliometric or scientometric analyses have become fundamental tools for analyzing current trends within the scientific literature and provide guidelines and motivations for future research in specific fields or areas. Recently, bibliometric analyses have been reported on eutrophication [17], diatom research [18], microcystins in China [19], photosynthesis [20] and microalgae research [21]. However, although these reports indirectly addressed dinoflagellate research, curiously this area has not been specifically emphasized-with the exception of Barbosa Noga and Ferreira Gomes [22] summarizing Brazilian dinoflagellate studies.…”
Section: Introductionmentioning
confidence: 99%
“…In bibliometric studies, keyword analysis, as core content summary of articles, has long been used to identify research focus in ecological disciplines [5,6,7,8,9,10]. Author keywords contain information that authors consider as most concerned and relevant to their studies, and high-frequency keywords are deemed to reflect the hot issues, and could be used to reveal the research trends [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%